PERANCANGAN SISTEM ANTRIAN TERINTEGRASI BERBASIS WEBSITE GUNA OPTIMALISASI PROSES LAYANAN DI KLINIK PRATAMA CITRA TAHUN 2024 - Tarigan, Raskhita (Jurnal Penelitian Kesmasy, 2024)
In Helping admins create queues to optimize the service system in the clinic, one of them that can help is computer technology, as a tool to provide queues to patients, store patient data and manage clinic queue data. The problem that exists in the Pratama Citra Clinic does not yet have a website for the patient queue system in the Clinic itself, The purpose of this study is to Design an Integrated Queue System Based on the Website to Optimize the Service Process at the Pratama Citra Clinic. method used by Watterfall. The results obtained from the respondents were to find out whether or not there were shortcomings of the website that had been designed, as well as to find out whether the website system that had been designed was accepted by the Pratama Citra Clinic or not. This study made a design using Microsoft Office Visio 2016 to create an Entity Relationship Diagram (ERD) and Data Flow Diagram (DFD). The integration and testing stages of the system of each unit of the program are integrated with each other and tested as a total system. Then it is sent to the system user. Testing websites that have been designed using Blackbox testing. The conclusion is that it can manage queues efficiently and increase the efficiency of the patient experience for clinical treatment. It is recommended to be able to develop this system according to what is needed to make it more perfect.